2023
DOI: 10.3390/cancers15041080
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Inflammatory Indices in Second-Line Soft Tissue Sarcoma Patients: Focus on Lymphocyte/Monocyte Ratio and Trabectedin

Abstract: A second-line standard of treatment has not yet been identified in patients with soft tissue sarcomas (STS), so identifying predictive markers could be a valuable tool. Recent studies have shown that the intratumoral and inflammatory systems significantly influence tumor aggressiveness. We aimed to investigate prognostic values of pre-therapy neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), lymphocyte-to-monocyte ratio (LMR), systemic inflammatory index (SII), progression-free survival… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 87 publications
0
28
0
Order By: Relevance
“…Interestingly, we identified the down-regulation of several immunoglobulin genes as well as down-regulation of neutrophil-mediated immunity and activation pathways in LR patients compared to LNR ones. These results are particularly interesting in light of recently published results, which showed that an increased neutrophils-to-lymphocyte ratio was significantly associated with worse PFS in a case series of 99 STS patients [ 6 ]. Indeed, it is known from the literature that neutrophils can remodel the extracellular matrix and promote angiogenesis, thereby stimulating tumor cell migration and metastasis.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Interestingly, we identified the down-regulation of several immunoglobulin genes as well as down-regulation of neutrophil-mediated immunity and activation pathways in LR patients compared to LNR ones. These results are particularly interesting in light of recently published results, which showed that an increased neutrophils-to-lymphocyte ratio was significantly associated with worse PFS in a case series of 99 STS patients [ 6 ]. Indeed, it is known from the literature that neutrophils can remodel the extracellular matrix and promote angiogenesis, thereby stimulating tumor cell migration and metastasis.…”
Section: Discussionmentioning
confidence: 77%
“…UPS is characterized by a transition from storiform to pleomorphic areas representing a highly variable morphology. Since no specific diagnostic biomarkers are currently available, the diagnosis is mainly based on the exclusion of other cancer histotypes e.g., dedifferentiated and pleomorphic liposarcoma, pleomorphic leiomyosarcoma, pleomorphic rhabdomyosarcoma, MFS, poorly differentiated carcinoma, and melanoma [ 6 ]. The standard of care for localized STS including MFS and UPS is represented by surgery combined with (neo)adjuvant radio and chemotherapy in selected cases.…”
Section: Introductionmentioning
confidence: 99%
“…A low lymphocyte-to-monocyte ratio (LMR) was associated with worse OS (p = 0.006). Interestingly, low lymphocyte-to-monocyte ratio (LMR) was an indicator of trabectedin efficacy, which could be applied in clinical practice ( 9 ). In a previous study in 2021, 3D-cultured cells from leiomyosarcoma and undifferentiated pleomorphic sarcoma (UPS) surgical specimens were treated with trabectedin and demonstrated the involvement of ECM-associated genes such as mmps and their inhibitor timp1 , emphasizing the potential role of ECM in the activity of trabectedin ( 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…7 Moreover, although there are reports that biomarkers, such as the neutrophil-to-lymphocyte ratio, platelet-to-lymphocyte ratio, lymphocyte-to-monocyte ratio, and systemic inflammatory index, which can be used as predictors of the prognosis in patients with STS, the information about the relationship between genetic mutations and overall survival is still insufficient. 26 Information about genetic mutations in tumor tissue is increasingly being used to help choose treatments for advanced STS. Memorial Sloan Kettering Cancer Center reported that clinical genomic profiling of bone and STS helped provide information crucial for targeted therapy for genetic mutations detected in 29% of patients.…”
Section: Introductionmentioning
confidence: 99%
“…However, it remains unclear which regimen is optimal for patients with non‐L‐sarcoma STS on an individual basis 7 . Moreover, although there are reports that biomarkers, such as the neutrophil‐to‐lymphocyte ratio, platelet‐to‐lymphocyte ratio, lymphocyte‐to‐monocyte ratio, and systemic inflammatory index, which can be used as predictors of the prognosis in patients with STS, the information about the relationship between genetic mutations and overall survival is still insufficient 26 …”
Section: Introductionmentioning
confidence: 99%